2020
DOI: 10.3389/fpls.2020.00319
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Crop Domestication Through Genomic Selection, a Case Study of Intermediate Wheatgrass

Abstract: Perennial grains could simultaneously provide food for humans and a host of ecosystem services, including reduced erosion, minimized nitrate leaching, and increased carbon capture. Yet most of the world's food and feed is supplied by annual grains. Efforts to domesticate intermediate wheatgrass (Thinopyrumn intermedium, IWG) as a perennial grain crop have been ongoing since the 1980's. Currently, there are several breeding programs within North America and Europe working toward developing IWG into a viable cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 72 publications
(80 reference statements)
2
34
0
Order By: Relevance
“…The low prediction value for spike yield could be due to the amount of environmental variance and genotype-byenvironment that impact this trait from year to year. Crain et al (2020a) showed similar results that traits with less genotypeby-environment interaction-free threshing and shattering-T A B L E 3 TLI-Cycle 7 traits measured in 2019 for two groups: validation population and the selected parents. The mean for each group is reported along with p value for group effect in the model.…”
Section: Effectiveness Of Gssupporting
confidence: 65%
“…The low prediction value for spike yield could be due to the amount of environmental variance and genotype-byenvironment that impact this trait from year to year. Crain et al (2020a) showed similar results that traits with less genotypeby-environment interaction-free threshing and shattering-T A B L E 3 TLI-Cycle 7 traits measured in 2019 for two groups: validation population and the selected parents. The mean for each group is reported along with p value for group effect in the model.…”
Section: Effectiveness Of Gssupporting
confidence: 65%
“…This collective effort to improve IWG also has resulted in a complete genome sequence ( Thinopyrum intermedium v2.1 DOE‐JGI, https://phytozome-next.jgi.doe.gov/info/Tintermedium_v2_1/). Both TLI and UMN researchers have been leveraging the genome sequence to significantly reduce their labor‐intensive phenotypic breeding schemes with genomic selection, which is a DNA marker‐ and statistics‐based selection approach (Bajgain et al., 2019a, 2020; Crain et al., 2020; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Forage varieties were included along with wild accessions in the starting population from which the Rodale Institute began its selections (Wagoner and Schauer, 1990). In the early 2000s, The Land Institute revived the intermediate wheatgrass domestication program and has since performed nine cycles of recurrent selection; three cycles have been completed at the University of Minnesota (Crain et al, 2020). Recent cycles of selection use genomic selection to accelerate genetic gains for domestication traits and cereal grain yield (Zhang et al, 2016).…”
Section: Value Of Recognizing Broad Genetic Changes Involved In Domesmentioning
confidence: 99%